Studies On The Mechanisms And Utilization Of Probiotics (Direct-Fed Microbials) In Broilers - Jin, Lizhi (1996)

(untitled)
A series of experiments were conducted to isolate and characterize suitable intestinal microbes as direct-fed microbials and to investigate their effects on broiler. and the mechanisms associated with their utilization. The major types of bacteria found in the duodenum and jeju-ileum of chicken were Lactobacillus, Streptococcus and E. coli. In the cecum, ten groups of bacteria, namely, Streptococcus, Staphylococcus, Lactobacillus, E. coli, anaerobic coccus, Eubacterium, Propiombacterium, Clostridium, Fusobacterium and Bacteroides were isolated and identified. The main Lactobacillus species in chicken intestine were L. acidophilus, L. fermentum and L. brevis In vitro adhesion study demonstrated that 1 2 out of the 46 intestinal Lactobacillus isolates showed moderate to good ability to adhere to the ileal epithelial cell of chicken. Temperature (between 4°C and 42°C) did not have an effect on the attachment of the Lactobacillus isolates to the ileal epithelial cell. Incubation (contact) time of 30 min was found to be insufficient for the attachment of bacterial to the ileal epithelial cell, but contact time extended beyond 1 h did not improve the ability of the bacteria to adhere to the ileal epithelial cell. The pH values of suspending buffer for the Lactobacillus strains, ranging from 4 to 7, did not have any significant effect on the attachment of the bacteria to the ileal epithelial cell, but pH 8 reduced significantly (p<0.05) the attachment of bacteria. The growth of the 12 adherent Lactobacillus isolates was inhibited only slightly by the inclusion of 0.3% chicken bile in the culture medium, and they all showed a tolerance (in varying degrees) to low pH values ( 1.0 or 2.0).